Paul J. Pelz papers - Pelz, Paul J., 1841-1918.
Correspondence, memoranda, reports, testimonials, printed matter, pictorial representations of buildings, drawings, photographs, and other papers relating to the planning and construction of the Library of Congress Jefferson Building and other buildings. Documents the claims of Pelz and John L. Smithmeyer against the federal government for architectural fees for the Library. Includes material concerning Pelz's investment in the Honduras Aurora Mining Company and other Latin American agricultural and mining ventures. Also includes photocopies of miniature portraits of his parents, Eduard Pelz and Henriette Pelz. Correspondents include Allen O. Clephane, Eugene Davis, Stephen B. Elkins, Owen Bert French, Julian Hurdle, William A. Robertson, and Elliott Woods.
Architect of the Library of Congress Jefferson Building. Born in Silesia; emigrated to the United States in 1858. Formed partnership with John L. Smithmeyer, 1873 (Smithmeyer & Pelz). Full name: Paul Johannes Pelz.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Library of Congress Archives.
Keywords: Clephane, Allen O. -- Correspondence; Davis, Eugene -- Correspondence; Elkins, Stephen B. -- 1841-1911 -- Correspondence; French, Owen Bert, -- 1865-1951 -- Correspondence; Hurdle, Julian -- Correspondence; Pelz, Eduard, -- 1800-1876.; Pelz, Henriette; Robertson, William A. -- Correspondence; Smithmeyer, John L., -- -1908 -- Claims vs. United States; Woods, Elliott, -- 1864-1923 -- Correspondence; Honduras Aurora Mining Company; Library of Congress; Smithmeyer & Pelz; Agriculture -- Latin America; Architecture -- Washington (D.C.); Libraries -- Washington (D.C.); Mines and mineral resources -- Honduras; Mines and mineral resources -- Latin America; Architects